Perioperative outcomes of open radical prostatectomy versus laparoscopic radical prostatectomy in Asian men: comparison of two initial series by the same surgeon - Sunai Leewansangtong; Wirat Wiangsakunna; Tawatchai Taweemankongsap (International Brazilian Journal of Urology, 2009)
PURPOSE: To compare the perioperative outcomes in 2 initial series of open radical prostatectomy (ORP) and laparoscopic radical prostatectomy (LRP) in Asian men with prostate cancer. MATERIAL AND METHODS: From March 1999 to February 2007, the first 100 consecutive patients who underwent ORP and the first 100 consecutive patients who underwent LRP by the same surgeon (SL) were assessed. Mean age, clinical stage, preoperative PSA level, Gleason score, operative time, estimated blood loss, blood transfusion rate, perioperative complications, pathological stage and margin status were compared between the 2 groups. RESULTS: For each 100 patients in ORP and LRP, mean age and clinical stage were not significantly different. The operative time in LRP was significantly longer than ORP (188 ± 55 versus 114 ± 31 minute, p value = 0.01). Mean estimated blood loss and blood transfusion rate in LRP was significantly lower than ORP, 521 ± 328 versus 809 ± 510 mL (p value = 0.03) and 27% versus 55% (p value = 0.01), respectively. For pathological organ confined disease, the free surgical margin rate of ORP and LRP was not significantly different (88.9% versus 91.3%, respectively, p = 0.58). There was no significant major complication in either group. CONCLUSIONS: For initial experience by a single surgeon, LRP is comparable to ORP with no significant morbidity. LRP had longer operative time. However, LRP decreased blood loss and blood transfusion. For localized prostate cancer, free surgical margin rate of ORP and LRP was not significantly different.